Discursive Symbolism in A Semiotic Approach on the Joker Movie Trailer - Adiella Yankie Lubis; Ilona Vincenovie Oisina (FISIP Universitas Atma Jaya Yogyakarta, 2022)
Movie trailers are powerful marketing tool to influence audiences. Joker is the most famous villain character in the DC world. Data shows that the Joker movie trailer uploaded by movie-themed verified YouTube accounts has been watched more than 71 million times in four months. The trailer is discussed through a semiotic perspective to analyze discursive symbols in a film trailer. The result shows that there are three main connotative meanings for Joker: (1) a good person who loves his mother, (2) the formation of his identity, and (3) the transformation from a good person to a criminal.